Shape discrimination thresholds among subjects with emmetropia and corrected myopia. (July 2015) - Rajeev, Narayanan; Tan, Eddie; Liyana, Raja; Metha, Andrew
<x xml:space="preserve">Abstract</x> Background Myopia is highly prevalent in some Asian countries yet the ability of subjects with myopia to discriminate shapes using radial frequency (RF) patterns—circular patterns that are defined by sinusoidal modulation of the radius in polar coordinates—is not well documented. In this psychophysical study, we explore the relative ability of subjects with corrected myopia to discriminate shapes using radial frequency patterns. Specifically, the aims were to find if there are any differences in modulation detection thresholds among subjects with emmetropia and corrected myopia and to establish thresholds as a function of myopic refractive error. Methods Shape discrimination thresholds were measured for subjects with emmetropia (n = 20) and corrected myopia (n = 20) using circular D4 (fourth derivative of Gaussian) radial frequency patterns. A total of five radial frequency patterns (RF1 to RF16) with peak spatial frequencies of 2, 4, 6 and 8 (SF2 to SF8) cycles per degree were studied. The radial frequency suffix determines the number of deformation cycles present around the circumference, while the peak spatial frequency is related to the thickness of the circular contour. Results Overall, shape discrimination thresholds were not significantly different (p > 0.05) between subjects with emmetropia and corrected myopia. Similarly, there was no significant correlation (p > 0.05) in thresholds with the magnitude of corrected myopia. Shape discrimination performance was best for RF8 patterns, with thresholds ranging from nine to 12 seconds of arc for SF2 to SF6 patterns and from 20 to 22 seconds of arc for SF8 patterns. Thresholds were significantly higher (p < 0.05) for SF8 patterns compared to the other spatial frequency patterns (SF2 to SF6) for all radial frequency patterns. The average thresholds increased by about 1 to 1.5 log units from RF1 to RF4 and RF8. Conclusion Across all patterns studied here, shape discrimination thresholds remain at hyperacuity levels and are not degraded in subjects with corrected myopia compared to emmetropia.